2023
DOI: 10.3390/w15061132
|View full text |Cite
|
Sign up to set email alerts
|

Mining Leachates Effect on the Hydraulic Performance of Geosynthetic Clay Liners under Different Temperatures

Abstract: Geosynthetic clay liners (GCLs) are often used as anti-seepage systems in landfills and at the bottom of tailing ponds. The anti-seepage performance of GCL will change under different temperatures. In this study, bentonite was mixed with test solutions at different temperatures to measure the basic performance indexes of bentonite components and analyze the permeability. The composition and micro-structure of bentonite at different temperatures were analyzed by X-ray diffraction, X-ray fluorescence spectrum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…For the intercrystalline phosphate impurities, Cai et al [74] illustrated that oxalic acid could eliminate part of cocrystalline phosphorus impurities by disrupting a portion of the gypsum crystal structure, resulting in the phosphorus leaching efficiency of 77.7% with the use of 1% oxalic acid. Although this method is easy to operate, it often requires a large amount of solution, which inevitably faces the problem of subsequent leachate treatment [75,76]. In addition, this method only removes surface-adsorbed impurities, with little effect on those encapsulated.…”
Section: Acid/alkali Leachingmentioning
confidence: 99%
“…For the intercrystalline phosphate impurities, Cai et al [74] illustrated that oxalic acid could eliminate part of cocrystalline phosphorus impurities by disrupting a portion of the gypsum crystal structure, resulting in the phosphorus leaching efficiency of 77.7% with the use of 1% oxalic acid. Although this method is easy to operate, it often requires a large amount of solution, which inevitably faces the problem of subsequent leachate treatment [75,76]. In addition, this method only removes surface-adsorbed impurities, with little effect on those encapsulated.…”
Section: Acid/alkali Leachingmentioning
confidence: 99%
“…The technical principle of seismic exploration is based on the differences of kinematic and dynamic characteristics of seismic wave propagation in stratum interface structure and media with different physical characteristics [21][22][23]. However, seismic exploration is easily affected by strong human interference, and obtaining high-quality data requires explosive sources, which may cause damage to the surrounding environment [24,25]. Geological radar method is a shallow geological advance prediction method, which uses the difference between the length of electromagnetic wave propagation time in the transport medium to determine the properties and occurrence of the geological body.…”
Section: Methods Selection For Karst Detectionmentioning
confidence: 99%
“…Numerous engineering examples have shown that the stability of drilled-shaft walls is influenced by various factors, with mud slurry protection playing a vital role [4]. Scholars have conducted theoretical analysis [5,6], laboratory experiments [7][8][9][10][11], field experiments [12][13][14], and numerical simulations [15][16][17][18] to study the issue of mud slurry protection and soil stability. The unreinforced and geogrid-reinforced soil foundations were modeled using a particle flow code of two dimensions (PFC2D) and the effects of four different factors on footing settlement were investigated [19].…”
Section: Introductionmentioning
confidence: 99%